Dimensiuni ale politicii culturale în perioada de tranziție - Costin, Cornelia (Calitatea Vieții, 1993)
The complexity of the transition period generates the need of political intervention within all the sections of the social system. In the field of culture these measures may cause some of the most unexpected or even ’perverse’ effects, because they imply not only on individuals, but on generations as a whole.